Students’ Learning Issues in Pakistan: A Study on English Language - Otho, Wakeel Ahmed; Shahzadi, Shagufta; Khatoon, Asia (Annals of Human and Social Sciences, 2023)
This study examines students’ English language learning in Pakistan, where it is widely spoken. English is taught as a mandatory subject at all educational levels in Pakistan, where it is utilized as both an official language and a foreign language.This study examines the elements that influence students’ adoption of an English language. Students struggle in school and college, resulting in a lack of understanding of many subjects since they must complete all of their studies in English. This exploratory study aims to determine the factors influencing learning another language among students in government schools. Students representing all levels of variables impacting English language acquisition were included in the data sample. The study’s findings recommended that students should focus on linguistic factors when learning another language. It is considered that someone’s motivation, attitude, age, IQ, aptitude, cognitive style, and personality all have a significant effect in how successfully they learn a second language